Molecular changes in pre-metastatic lymph nodes of esophageal cancer patients. - Benjamin Otto; Alexandra M Koenig; Genrich V Tolstonog; Anke Jeschke; Kristin Klaetschke; Yogesh K Vashist; Daniel Wicklein; Christoph Wagener; Jakob R Izbicki; Thomas Streichert (PLoS ONE, 2014)
Lymph node metastasis indicates poor prognosis in esophageal cancer. To understand the underlying mechanisms, most studies so far focused on investigating the tumors themselves and/or invaded lymph nodes. However they neglected the potential events within the metastatic niche, which precede invasion. Here we report the first description of these regulations in patients on transcription level. We determined transcriptomic profiles of still metastasis-free regional lymph nodes for two patient groups: patients classified as pN1 (n = 9, metastatic nodes exist) or pN0 (n = 5, no metastatic nodes exist). All investigated lymph nodes, also those from pN1 patients, were still metastasis-free. The results show that regional lymph nodes of pN1 patients differ decisively from those of pN0 patients--even before metastasis has taken place. In the pN0 group distinct immune response patterns were observed. In contrast, lymph nodes of the pN1 group exhibited a clear profile of reduced immune response and reduced proliferation, but increased apoptosis, enhanced hypoplasia and morphological conversion processes. DKK1 was the most significant gene associated with the molecular mechanisms taking place in lymph nodes of patients suffering from metastasis (pN1). We assume that the two molecular profiles observed constitute different stages of a progressive disease. Finally we suggest that DKK1 might play an important role within the mechanisms leading to lymph node metastasis.